Erratum: MONNÉ M.M. (2012) Catalogue of the type-species of the genera of the Cerambycidae, Disteniidae, Oxypeltidae and Vesperidae (Coleoptera) of the Neotropical Region . Zootaxa, 3213, 1–183. - Monné, M. M. (Zootaxa, 2012)
(Erratum)